Climate-Adapted Circular Poultry Production: Salt-Treated Wild Yam Tubers as Sustainable Supplementary Feed Ingredients Via Osmosis-Based Detoxification - Taer, Erma; Cordova , Siony (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Wild yams have tremendous potential as nutritious food and feed sources. However, anti-nutritional factors like oxalates and phenolics limit their utilization. This study evaluated salt-assisted osmosis for detoxification and nutritional improvement of wild yam tubers and assessed their application as a feed ingredient for native chickens. Wild yam tubers were treated with 10%, 20%, and 30% salt solutions to induce osmosis-based leaching of water-soluble toxins. Proximate analyses confirmed nutrient retention post-treatment. Four isonitrogenous experimental chicken feeds were formulated with varying proportions of standard commercial diet and salt-treated wild yam meal. Ninety-six 5-week-old native chicks were randomly allocated to the diets for 8 weeks to assess growth performance, intake, meat quality, and physiological parameters. Toxin levels decreased up to 50% with a 30% salt solution while beneficial nutrients were preserved. The inclusion of treated yam meal did not adversely affect growth rate, though higher salt levels reduced feed palatability. Carcass traits remained unaffected although minor organ weight and serum biomarker changes indicated physiological stress. Salt-assisted osmosis the demonstrates potential for efficient detoxification to promote better utilization of under-explored nutritious crops like wild yam as sustainable, alternative feed sources without compromising nutritional adequacy. Further optimization to prevent anti-nutrient reaccumulation and physiological imbalance is recommended before scalability for food/feed security.